2018
DOI: 10.1051/matecconf/201822506004
|View full text |Cite
|
Sign up to set email alerts
|

Metal Injection Molding Process Parameters as A Function of Filling Performance of 3D Printed Polymer Mold

Abstract: Metal injection molding (MIM) is a swift manufacturing process, which can produce complex and intricate parts with good repeatability and accuracy. However, to quickly address low-volume demands of customized MIM parts, manufacturing of mold could be a potential challenge. Typically, machined metal molds are used for MIM, but they are expensive and need more lead time. The machined metal mold becomes useless once the design is changed or requirement of MIM parts is met. Therefore, for MIM production of a low v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Confidence to fill, resulting from Moldflow ( Figure 3 a), revealed that the entire body of the green part has high value (green color) and no indication of the occurrence of short shot. It was suggested that processing conditions were deemed incorrect if confidence of fill result was low [ 24 ]. One of the Moldflow results is pressure drop, as shown in Figure 3 b.…”
Section: Resultsmentioning
confidence: 99%
“…Confidence to fill, resulting from Moldflow ( Figure 3 a), revealed that the entire body of the green part has high value (green color) and no indication of the occurrence of short shot. It was suggested that processing conditions were deemed incorrect if confidence of fill result was low [ 24 ]. One of the Moldflow results is pressure drop, as shown in Figure 3 b.…”
Section: Resultsmentioning
confidence: 99%